The primacy of politics : social democracy and the making of Europe's twentieth century - Berman, Sheri (Cambridge University Press, 2020)
Political history in the industrial world has indeed ended, argues this pioneering study, but the winner has been social democracy - an ideology and political movement that has been as influential as it has been misunderstood. Berman looks at the history of social democracy from its origins in the late nineteenth century to today and shows how it beat out competitors such as classical liberalism, orthodox Marxism, and its cousins, Fascism and National Socialism by solving the central challenge of modern politics - reconciling the competing needs of capitalism and democracy.